Development of tools to facilitate palliative and supportive care referral for patients with idiopathic pulmonary fibrosis. Issue 3 (30th June 2017) - Sharp, Charles; Lamb, Heather; Jordan, Nikki; Edwards, Adrienne; Gunary, Rachel; Meek, Patricia; Millar, Ann B; Kendall, Clare; Adamali, Huzaifa
Abstract : Objectives: Palliative care is underused in non-malignant respiratory diseases, including interstitial lung diseases (ILDs). We investigated current practices around palliative and supportive care and explored the impact of a supportive care decision aid tool. Methods: This was a single centre study in a UK ILD centre. Retrospective analysis of hospice referrals and patients with idiopathic pulmonary fibrosis (IPF) under the Bristol ILD (BILD) service were used to identify unmet palliative and supportive care needs. Using quality improvement methodology, we explored the impact of a supportive care decision aid on clinician behaviours for patients with ILD. Results: 108 patients with ILD were referred for hospice care between 2010 and 2015, representing 0.15% of all referrals, compared with a population prevalence of IPF of 0.9%. The median interval between referral and death was 124 days. Records were reviewed for 64 deceased and 89 living patients with IPF seen on July–December 2014. The decision aid was prospectively assessed with 73 patients. The deceased patients had greater markers of severity. There were no other differences between the groups. After introduction, the decision aid tool was completed for 49.3% of patients and resulted in significant increases in documented discussion of referral to palliative care (11.2%vs53.6%, p<0.01) and end-of-life discussions (15.7%vs91.8%, p<0.01). Tool completion led to an increase in referral for palliative care (2.7%vs16.7%, p<0.01). Conclusion: Palliative care services are underused in ILD and a supportive care decision aid can prompt consideration of palliative and supportive care needs.